Effects of Long-Term Nitrogen Fertilization on Nitrous Oxide Emission and Yield in Acidic Tea (Camellia sinensis L.) Plantation Soils - Fuying Jiang; Yunni Chang; Jiabao Han; Xiangde Yang; Zhidan Wu (Agronomy)
The responses of nitrous oxide (N2O) emissions to nitrogen (N) application in acidic, perennial agricultural systems, and the factors driving these emissions, remain poorly understood. To address this gap, a 12-year field experiment was conducted to investigate the effects of different N application rates (0, 112.5, 225, and 450 kg N ha−1 yr−1) on N2O emissions, tea yield, and the associated driving factors in a tea plantation. The study found that soil pH significantly decreased with long-term N application, dropping by 0.32 to 0.85 units. Annual tea yield increased significantly, by 148–243%. N application also elevated N2O emission fluxes by 33–277%, with notable seasonal fluctuations observed. N2O flux was positively correlated with N rates, water-filled pore space (WFPS), soil temperature (Tsoil), and inorganic N (NH4+-N and NO3−-N), while showing a negative correlation with soil pH. Random forest (RF) modeling identified WFPS, N rates, and Tsoil as the most important variables influencing N2O flux. The cumulative N2O emissions for N112.5, N225, and N450 were 1584, 2791, and 45,046 g N ha−2, respectively, representing increases of 1.33, 2.34, and 3.77 times compared to N0. The N2O-N emission factors (EF) were 0.35%, 0.71%, and 0.74%, respectively, and increased with higher N rates. These findings highlight the importance of selecting appropriate fertilization timing and improving water and fertilizer management as key strategies for mitigating soil acidification, enhancing nitrogen use efficiency (NUE), and reducing N2O emissions in acidic tea-plantation systems. This study offers a theoretical foundation for developing rational N fertilizer management practices and strategies aimed at reducing N2O emissions in tea-plantation soils.